2010
DOI: 10.21608/jvmr.2020.77612
|View full text |Cite
|
Sign up to set email alerts
|

Trial for preparation and evaluation of combined vaccine against ND, IB and M. gallisepticum diseases in chickens

Abstract: In this study, a combined Trivalent vaccine against ND, IB and M. gallisepticum was locally prepared and evaluated in comparison with other locally prepared Bivalent ND and IB and monovalent M. gallisepticum vaccines. The obtained results were promising for this locally prepared Trivalent vaccine and the immune response was outstanding starting at the 2 nd week post vaccination and showed extended raising allover the experiment period. The immune response of chickens vaccinated with the Trivalent was shoot up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Our finding indicated that when used vaccinal program as classical IB48 and variant IB primer give high antibody titer than when used MA5+4/91 or H120+CR88 under condition of our experiment. This results come in agreement with (Pensaert and Lambrechts 1994), (Alvarado et al , 2003), (Hamel et al, 2006) , (Martin et al, 2007) , (Salma et al, 2010) and (susanet al, 2011) they compare ELISA antibody level in birds vaccinated with commercial classical or variant IB vaccine also vaccine prepared from local isolated variant IB strain related to 4/91 which gave high level of antibody than commercial classical vaccine.…”
supporting
confidence: 88%
“…Our finding indicated that when used vaccinal program as classical IB48 and variant IB primer give high antibody titer than when used MA5+4/91 or H120+CR88 under condition of our experiment. This results come in agreement with (Pensaert and Lambrechts 1994), (Alvarado et al , 2003), (Hamel et al, 2006) , (Martin et al, 2007) , (Salma et al, 2010) and (susanet al, 2011) they compare ELISA antibody level in birds vaccinated with commercial classical or variant IB vaccine also vaccine prepared from local isolated variant IB strain related to 4/91 which gave high level of antibody than commercial classical vaccine.…”
supporting
confidence: 88%